(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Research and Development (R&D) research with the ADDIE model which includes five stages, namely Analyze, Design, Development, Implementation, and Evaluation. This research aims to develop a valid, practical, and effective Wayground-based interactive media-based IPAS learning tool. The test subjects in this study were 36 students of class V-A SDN V Surabaya. The results of the validity of the learning tools showed excellent quality based on the experts’ assessments, with the percentage of Wayground media experts of 92% (very valid), material experts of 90% (very valid), teaching modules of 87% (very valid), evaluation of 89% (very valid), and assessment instruments and rubrics of 80% (valid), so that all components were declared very suitable for use. Meanwhile, the practicality criteria measured through the student response questionnaire obtained a result of 90.27% (very practical) and the observation of student activities reached a total score of 46 (very practical), indicating that this device is easy and efficient to apply in the classroom. In terms of effectiveness, the use of Wayground media has succeeded in significantly improving the learning outcomes of students in class V-A, as seen from the increase in the average score from pretest of 63.33 to posttest of 89.58, which is strengthened by the acquisition of an N-gain index of 0.71 (high category). Thus, it can be concluded that the development of IPAS learning tools through Wayground ineractive media at SDN V Surabaya has proven to be valid, practical, and effective in improving student learning outcomes.